Plant grafting: new mechanisms, evolutionary implications - Goldschmidt, Eliezer E. (Frontiers in Plant Science, 2014)
Grafting, an old plant propagation practice, is still widely used with fruit trees and in recent decades also with vegetables. Taxonomic proximity is a general prerequisite for successful graft-take and long-term survival of the grafted, composite plant. However, the mechanisms underlying interspecific graft incompatibility are as yet insufficiently understood. Hormonal signals, auxin in particular, are believed to play an important role in the wound healing and vascular regeneration within the graft union zone. Incomplete and convoluted vascular connections impede the vital upward and downward whole plant transfer routes. Long-distance protein, mRNA and small RNA graft-transmissible signals currently emerge as novel mechanisms which regulate nutritional and developmental root/top relations and may play a pivotal role in grafting physiology. Grafting also has significant pathogenic projections. On one hand, stock to scion mechanical contact enables the spread of diseases, even without a complete graft union. But, on the other hand, grafting onto resistant rootstocks serves as a principal tool in the management of fruit tree plagues and vegetable soil-borne diseases. The ‘graft hybrid’ historic controversy has not yet been resolved. Recent evidence suggests that epigenetic modification of DNA-methylation patterns may account for certain graft-transformation phenomena. Root grafting is a wide spread natural phenomenon; both intraspecific and interspecific root grafts have been recorded. Root grafts have an evolutionary role in the survival of storm-hit forest stands as well as in the spread of devastating diseases. A more fundamental evolutionary role is hinted by recent findings that demonstrate plastid and nuclear genome transfer between distinct Nicotiana species in the graft union zone, within a tissue culture system. This has led to the formation of alloploid cells that, under laboratory conditions, gave rise to a novel, alloploid Nicotiana species, indicating that natural grafts may play a role in plant speciation, under certain circumstances.